Tenofovir has inferior efficacy in adefovir-experienced chronic hepatitis B patients compared to nucleos(t)ide-naïve patients - Goh Eun Chung; Eun Ju Cho; Jeong-Hoon Lee; Jeong-ju Yoo; Minjong Lee; Yuri Cho; Dong Hyeon Lee; Hwi Young Kim; Su Jong Yu; Yoon Jun Kim; Jung-Hwan Yoon; Fabien Zoulim (Clinical and Molecular Hepatology, 2017)
Background/Aims A recent study reported that entecavir had inferior efficacy in nucleos(t)ide analogue (NA)-experienced chronic hepatitis B (CHB) patients compared to NA-naïve patients. We sought to compare the efficacy of tenofovir disoproxil fumarate (TDF) in NA-experienced and NA-naïve CHB patients. Methods We retrospectively enrolled 252 consecutive patients who had a serum hepatitis B virus (HBV) DNA level greater than 2,000 IU/mL at the initiation of TDF treatment and who received TDF for at least 6 months. Complete virologic suppression (CVS) was defined as undetectable serum HBV DNA. We generated a multivariate Cox proportional-hazard model to examine predictive factors that were independently associated with time to CVS. Results The mean age of patients was 48.2 years, and the cohort included 181 NA-naïve patients and 71 NA-experienced patients. The median duration of TDF treatment was 14.4 (interquartile range, 9.5-17.8) months. A total of 167 (92.3%) of 181 NA-naïve patients achieved CVS, and 60 (84.5%) of 71 NA-exposed patients achieved CVS. Forty-nine (89.1%) of 55 patients who previously took an NA aside from adefovir and 11 (68.8%) of 16 adefovir-experienced patients achieved CVS. In multivariable analysis, previous adefovir exposure significantly influenced time to CVS (hazard ratio, 0.37; 95% confidence interval, 0.19-0.72; P=0.003), after adjusting for HBeAg positivity, baseline HBV DNA level and cirrhosis. Conclusions Tenofovir had inferior efficacy in adefovir-experienced CHB patients compared to NA-naïve patients. The response of patients with previous adefovir exposure to TDF monotherapy should be monitored closely.